(3cJGH GdUHQ hGdQVGs - (3CHh YHO Gddg GdMGQK Hf CSO GdeMGSHj, GdMGQK GdeMGSHj,J (B243 (3g` s
(3ChdgG (B:s
(3MJi dGjMH Cf jchf fbUg efg TjFkG ceG bGd ShjO Hf eJYHI eZJHWkG Hg aPdc fGadg s
(3BNQgG (B:s
(3hbGd eYGP Hf LHd YfO GdehJ CTOO Mfbc hQhi Nfbi HJNjbc aEfc JYde Cfi CMHc Je cJGH GdUHQ hGdQVG ddeMGSHi hGdMeO ddg QH GdYGdejf s
(3bWYI efgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B153 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B517s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs